The Development of Covey Trust Concepts Inside University - Gamayanto, indra; Sukamto, Titien; Nugraha, Rizka; Rohmani, Asih; WM, Ibnu Utomo; Syukur, Abdul (EDUTECH, 2018)
Universities and education are important factors that need to be taken very seriously as the pro-cess will produce useful human resources to create useful progress for the community. The 8th Habits Method is one of the most proven methods to apply at the University level, especially to lecturers and students. Applying The 8th Habits Method is a big challenge that deserves to be accepted because it will result in the discovery of the purpose of life or the sound (meaning) of self as we know that there are many students (millennial generation) who do not have it and this may also happen to the lecturer. Dr Maggie Gilewicz in her book entitles Why Young Adults Don’t Know What to Do With Their Lives And What Can Be Done About It? argues that students and young adults do not know how they spend their life time because nothing can encourage them and no support from the environment (Gilewicz, 2017). On the other hand, parents focus on build-ing the millennial children’ self-esteem and always protect them from disappointments (Vance and Stephens, 2010). This paper offers some hypothesis and its application to the lecturers and students because both cannot be separated and should work in synergy to achieve The 8th Habits. Internal and external influences are also things that need to be examined and responded positively as these are two factors that can be one of the inhibiting factors in applying The 8th Habits-Covey trust systems. Finally, it is important that lecturers and students keep learning to be able to think and be positive, creative and flexible to be able to apply The 8th Habits-covey trust systems. Universitas dan pendidikan adalah faktor penting yang harus disikapi dengan sangat serius meng-ingat kedua factor ini akan menghasilkan sumber daya manusia yang berguna untuk menciptakan kemajuan dalam masyarakat. The 8th Habits Method merupakan salah satu metode yang paling terbukti dapat diterapkan di tingkat perguruan tinggi, khususnya pada dosen dan mahasiswa. Pen-erapan The 8th Habits Method adalah suatu tantangan besar yang harus dihadapi karena akan berujung pada penemuan tujuan hidup atau makna diri karena sebagaimana yang kita ketahui ban-yak mahasiswa (generasi millennial) yang tidak memilikinya dan hal sama dapat pula terjadi pada dosen. Dr Maggie Gilewicz dalam bukunya yang berjudul Why Young Adults Don’t Know What to Do With Their Lives And What Can Be Done About It? berpendapat bahwa maha-siswa dan remaja dewasa tidak mengetahui bagaimana mereka akan menghabiskan masa hidup mereka karena tidak ada yang mendukung mereka termasuk dukungan dari lingkungan (Gilewicz, 2017). Di sisi lain, orangtua terpaku pada bagaimana agar anak-anak mereka dapat menghargai diri mereka dan selalu melindung mereka dari hal-hal yang dapat mengecewakan mereka (Vance and Stephens, 2010). Artikel ini menawarkan hipotesis dan aplikasinya pada dosen dan mahasiswa kerena keduanya tidak terpisahkan dan harus bersinergi untuk mencapai The 8th Habit. Pengaruh internal dan eksternal penting pula untuk diketahui dan direspon secara positif karena dua faktor ini dapat menjadi penghalang penerapan The 8th Habit-Covey trust systems. Oleh karena itu, penting bagi dosen dan mahasiswa untuk terus belajar agar dapat berpikir dan menjadi positif, kreatif, dan fleksibel sehingga dapat menerapkan The 8th Habit-Covey trust systems.